French grammar for dummies - Mazet, Véronique (For dummies, 2013)
The easy way to master French grammar French Grammar For Dummies is a logical extension and complement to the successful language learning book, French For Dummies. In plain English, it teaches you the grammatical rules of the French language, including parts of speech, sentence construction, pronouns, adjectives, punctuation, stress and verb tenses, and moods. Throughout the book, you get plenty of practice opportunities to help you on your goal of mastering basic French grammar and usage. Grasp the grammatical rules of French including parts of speech, sentenc.